2007
DOI: 10.2527/jas.2006-549
|View full text |Cite
|
Sign up to set email alerts
|

Fertility traits in spring-calving Aberdeen Angus cattle. 1. Model development and genetic parameters1

Abstract: Calving records (n = 6,763) obtained from first, second, and third parities of 3,442 spring-calving, Uruguayan Aberdeen Angus cows were used to estimate heritabilities and genetic correlations for the linear trait calving day (CD) and the binary trait calving success (CS), using models that considered CD and CS at 3 calving opportunities as separate traits. Three approaches were defined to handle the CD observations on animals that failed to calve: 1) the cows were assigned a penalty value of 21 d beyond the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 19 publications
3
38
2
Order By: Relevance
“…Most previous studies on the genetics of reproductive performance in beef cattle are limited in size (Evans et al, 1999;Phocas and Sapa, 2004;Bormann et al, 2006;Urioste et al, 2007) and therefore have large associated SE of estimated parameters. The objective of this study was to estimate genetic parameters for reproductive traits, especially pertinent to seasonal calving beef production systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies on the genetics of reproductive performance in beef cattle are limited in size (Evans et al, 1999;Phocas and Sapa, 2004;Bormann et al, 2006;Urioste et al, 2007) and therefore have large associated SE of estimated parameters. The objective of this study was to estimate genetic parameters for reproductive traits, especially pertinent to seasonal calving beef production systems.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low heritability commonly reported for most measures of reproductive performance in beef (Koots et al, 1994;Martínez-Velázquez et al, 2003;Donoghue et al, 2004) and dairy (Pryce and Veerkamp, 2001;Berry et al, 2013) cattle, the genetic variation present is sufficiently large enough (Gutiérrez et al, 2002;Berry et al, 2003;Goyache et al, 2005) to ensure breeding programs for reproductive performance are successful. Although many studies have attempted to quantify the proportion of phenotypic differences in reproductive performance among beef animals due to additive genetic effects, these studies have generally been limited in the number of animals or herds included in the analysis (Evans et al, 1999;Phocas and Sapa, 2004;Urioste et al, 2007). Furthermore, few (Gregory et al, 1995;Roughsedge et al, 2005;Gutiér-rez et al, 2007) evaluated the impact on reproduction caused by genetic selection on other economically important traits; these studies were generally limited in size and therefore lack precision in the estimates of especially the genetic correlations.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing DO in Spanish Holsteins, González-Recio et al (2006) found that CLM provided greater variances than LM (without penalty), but also provided greater heritability. Urioste et al (2007a) analyzed days to calving in beef cattle and showed that heritabilities estimated using LM and CLM were similar, whereas lower heritability was estimated using TLM by assigning censored records as missing. In the present study, the Weibull proportional hazard model produced an unconvincingly high heritability estimate, indicating that the model did not fit the data well.…”
Section: Variance Components and Heritabilitymentioning
confidence: 99%
“…In addition, frailty survival models have been applied to analyze fertility traits (Schneider et al, 2005(Schneider et al, , 2006. Another alternative is to use a threshold-linear model, which includes a binary trait indicating censoring status of the observations, and a continuous fertility trait (Donoghue et al, 2004c;Urioste et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Submission rate is also useful in seasonal calving/breeding production systems to describe whether or not an animal was submitted for service in a given period from the initiation of the herd breeding season . Calving rate is sometimes used in beef genetic evaluations (Johnston and Bunter, 1996;Urioste et al, 2007).…”
Section: Reproductive Phenotypes Used In Animal Breedingmentioning
confidence: 99%